The follow-up of patients with celiac disease - Marco Di Tola; Hetty J. Bontkes; Juan Irure-Ventura; Marcos López-Hoyos; Nicola Bizzaro (Journal of Translational Autoimmunity)
Celiac disease (CD) is a very common immune-mediated enteropathy resulting from the interaction between dietary gluten and the immune system in genetically predisposed individuals. The immune response leads to intestinal damage, malabsorption and, ultimately, to a broad spectrum of both intestinal and extra-intestinal symptoms. According to current criteria, a proper diagnosis of CD requires an initial phase consisting of clinical case identification and serological screening that, over time, has increased in importance. In most adults and in selected children, the diagnosis is subsequently defined by histological evidence of intestinal damage as a confirmatory test, which usually returns to normal after a suitable period of a gluten-free diet (GFD). The clinical remission and disappearance of circulating antibodies after a GFD further confirm the diagnosis and represent a goal to be achieved to improve the quality of life and reduce the risk of long-term complications. However, although the diagnostic criteria for CD are well defined and described in specific guidelines, the monitoring of CD patients undergoing GFD has been less studied and, consequently, specific guidelines for this phase are still lacking. The aim of this report was to evaluate the classical tools used to monitor the adherence and response to GFD, other non-invasive biomarkers that have been proposed for CD monitoring, and the histological follow-up of CD patients in order to provide a starting point for future discussions on this specific topic.